Prokrustova postelja nacionalizma in nove poti do razumevanja glasbene preteklosti Slovenije - Nagode, Aleš (Muzikološki zbornik, 2015)
Some of Slovene historiographers have in recent years discarded the nationalistic view of Slovene history, which has been predominant since 19th century. Author tries to explore the significance and usefulness of this line of research in modern Slovene music historiography.
Keywords: etnogeneza; glasbeno zgodovinopisje; metodologija; Slovenija